Construction of a New 3D Cu(II) Compound with Photocatalytic Activity and Therapeutic Effect on Ventriculitis - Xingzhao Chen; Qing Mao (Journal of Chemistry)
A new Cu(II) compound, that is {[Cu(L)(ClO4)(H2O)(CH3CN)](ClO4)}n (1, L is 4-(furan-2-yl)-2,6-bis(pyridin-2-yl)pyridine), was solvothermally synthesized and structurally characterized. It features a 0D isolated unit, and these 0D isolated units are further hydrogen-bonded into a 3D supramolecular framework. The framework of 1 can be stable up to 284°C, and the optical band gap of 1 is 3.71 eV. Under the irradiation of ultraviolet light, complex 1 as a photocatalyst exhibits high activity for methylene blue (MB) degradation in the water solution. The above compound’s inhibitory activity on the inflammatory cytokines releasing was tested through exploiting ELISA detection. The real time RT-PCR was conducted to assess the compound’s suppression on the expression of bacterial survival gene.